(untitled) (Journal of the College of Education for Women, 2019)
The Importance of Effort and its Impact in Building the Society in the Light ofthe Holy Book and Sunna.Thank for God and peace be upon Prophet Muhammad, His hose hold andCompanions.This research is to refute a fault : that Islam as a religioncalls for laziness anddependence and this in first, Second, to show the originality of the Islamic method inbuilding and construction.This research Starts with an introduction in which I refer to the nature of theIslamic method and its way of work in life: that it is a divine method that is achievedby the effort of the people them selfves and not through a divine extraordinary power:The research explains the shift in the peoples life who were addressed by thisQuran through the new concepts it presents.This Holy Quran calls people to work fast, to forego and to compete; it givesmany examples that instigate people to work and it explains to people how manshould move to get the goal he is looking for.In addition , the sayings of prophet Muhammad –peace be upon him- refer tothe importance of effort and its impact in building the society, These sayings are putwithin axes to make the picture clearer and such axes include:1. Sayings that refer to the importance of work to satisfy mans needs.2. Sayings that refer to the earth recoustruction and the importance ofimplantation.3. Sayings that guide the Muslim to work for the good.4. Sayings that call for discarding superstitions, illusions that prevent him fromdoing what he intends or plans to do.